Magneto-optics of layers of semiconductor quantum dots and nano-rings - Voskoboynikov,O. (2006)
We have studied the collective magneto-optical response of layers of semiconductor quantum dots and nano-rings. Expressions for both the polarizability of the individual nano-objects have been used to determine the magneto-optical response on square two-dimensional lattices on those nano-objects as a function on frequency, magnetic field and angle of incidence. The magnetic field dependence of the response for layers of rings gives rise to the Aharonov-Bohm type oscillatory behavior in the reflectance and absorbance that can be measurable. Layers of dots do not display any remarkable magnetic field dependence.